Dissolution-precipitation growth of uniform and clean two dimensional transition metal dichalcogenides. Issue 3 (30th May 2020) - Cai, Zhengyang; Lai, Yongjue; Zhao, Shilong; Zhang, Rongjie; Tan, Junyang; Feng, Simin; Zou, Jingyun; Tang, Lei; Lin, Junhao; Liu, Bilu; Cheng, Hui-Ming
Abstract: Two dimensional transition metal dichalcogenides (TMDCs) have attracted much interest and shown promise in many applications. However, it is challenging to obtain uniform TMDCs with clean surfaces, because of the difficulties in controlling the way the reactants are supplied to the reaction in the current chemical vapor deposition growth process. Here, we report a new growth approach called 'dissolution-precipitation' (DP) growth, where the metal sources are sealed inside glass substrates to control their feeding to the reaction. Noteworthy, the diffusion of metal source inside glass to its surface provides a uniform metal source on the glass surface, and restricts the TMDC growth to only a surface reaction while eliminating unwanted gas-phase reaction. This feature gives rise to highly uniform monolayer TMDCs with a clean surface on centimeter-scale substrates. The DP growth works well for a large variety of TMDCs and their alloys, providing a solid foundation for the controlled growth of clean TMDCs by the fine control of the metal source. Abstract : 2D materials with good quality and ultraclean surface were obtained by a universal dissolution-precipitation growth method that precisely controls the metal source and restricts the growth of materials to surface reaction.